On the contributions of photorespiration and compartmentation to the contrasting intramolecular2H profiles of C3and C4plant sugars - Zhou, Y.; Zhang, B.; Stuart-Williams, H.; Grice, Kliti; Hocart, C.; Gessler, A.; Kayler, Z.; Farquhar, G. (Pergamon, 2018)
© 2017 Elsevier Ltd Compartmentation of C 4 photosynthetic biochemistry into bundle sheath (BS) and mesophyll (M) cells, and photorespiration in C 3 plants is predicted to have hydrogen isotopic consequences for metabolites at both molecular and site-specific levels. Molecular-level evidence was recently reported (Zhou et al., 2016), but evidence at the site-specific level is still lacking. We propose that such evidence exists in the contrasting 2 H distribution profiles of glucose samples from naturally grown C 3 , C 4 and CAM plants: photorespiration contributes to the relative 2 H enrichment in H 5 and relative 2 H depletion in H 1 & H 6 (the average of the two pro-chiral Hs and in particular H 6, pro-R ) in C 3 glucose, while 2 H-enriched C 3 mesophyll cellular (chloroplastic) water most likely contributes to the enrichment at H 4 ; export of (transferable hydrogen atoms of) NADPH from C 4 mesophyll cells to bundle sheath cells (via the malate shuttle) and incorporation of 2 H-relatively unenriched BS cellular water contribute to the relative depletion of H 4 & H 5 respectively; shuttling of triose-phosphates (PGA: phosphoglycerate dand DHAP: dihydroacetone phosphate) between C 4 bundle sheath and mesophyll cells contributes to the relative enrichment in H 1 & H 6 (in particular H 6, pro-R ) in C 4 glucose.